The Problem of Evil and the Christian Hope: A Philosophical Exploration of Suffering in the Light of the Cross - Maria Theresia Lintang Wulandari (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2024)
The problem of evil remains one of the most persistent and challenging issues in Christian philosophy. This paper explores the philosophical dimensions of suffering through a Christian lens, focusing on the paradox of divine goodness in the presence of moral and natural evil. Drawing from classical theodicy and contemporary Catholic thought, the study examines how the mystery of the Cross offers a unique theological and philosophical response to suffering. Special attention is given to the thought of Augustine, Aquinas, and modern Catholic philosophers such as Henri de Lubac and Josef Pieper. The paper argues that Christian philosophy does not attempt to explain away suffering but rather provides a framework in which suffering can be redemptive, meaningful, and even transformative when united with the suffering of Christ. By grounding human suffering within the narrative of salvation history, Christian philosophy affirms that evil does not have the final word. The research also reflects on the existential implications of hope, patience, and grace in enduring suffering, making a case for a distinctly Christian metaphysical response to theodicy. This study contributes to ongoing discussions in Christian existentialism, ethics, and metaphysics by reaffirming the coherence of faith and reason in addressing one of the deepest human questions.